A pole piece and a method for preparing the same
Through dry mixing and stamping forming technology, the problems of traditional pole sheet manufacturing process are solved, high energy consumption and material waste are achieved, and the efficient and low-cost preparation of pole sheets is achieved, which significantly reduces the usage of copper-aluminum substrates and solvents Consumption.
Patent Information
- Application Number
- CN202410637081.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-05-22
AI Technical Summary
The traditional electrode sheet manufacturing process takes a long time, high energy consumption, and the use of a large number of copper and aluminum foil substrates cannot effectively streamline the process and reduce material costs.
The active substance powder, binder, conductive agent and metal wire are mixed by dry mixing method to form a solid substance mixture, and agitate into a viscous material without solvent. The wet electrode sheet is obtained by stamping and pressing after drying. To a thickness of 0.05-5mm, the preparation of the pole sheet is achieved.
The electrode sheet manufacturing process has been greatly reduced, the solvent usage and energy consumption have been reduced, the copper-aluminum substrate usage has been significantly reduced, the production efficiency and material utilization have been improved, and the efficient electrode sheet preparation has been achieved.
Smart Images

Figure CN118610387B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery materials, and specifically relates to a pole piece and a preparation method thereof. Background Art
[0002] Pole sheet design and manufacturing are key processes in the production of lithium batteries. The traditional pole sheet manufacturing process involves slurrying, coating, cold pressing and other processes. The formed pole sheet contains a copper-aluminum foil substrate and an active material membrane layer. The traditional pole sheet manufacturing process is time-consuming and energy-intensive, and a large amount of copper-aluminum foil substrate is used in pole sheet forming. According to calculations, the mass proportion of copper foil in the negative electrode sheet is 20%-30%, and the mass proportion of aluminum foil in the positive electrode sheet is 8%-15%. Therefore, streamlining the pole sheet manufacturing process and reducing the use of copper-aluminum substrates are the main directions for optimizing current pole sheet manufacturing.
[0003] Traditional electrode manufacturing involves mixing the active materials evenly using a wet method and then coating them on the current collector to prepare a 50-200μm thick electrode, which is then cold pressed and die-cut to obtain the final electrode. This preparation method involves many processes and is time-consuming. In addition, a large amount of solvent is consumed in the slurry process, and the coating process also requires high energy consumption to dry and volatilize the solvent in the electrode.
[0004] 24M, founded by MIT materials science professor Jiang Yeming, has developed a thick electrode technology that greatly increases the thickness of the electrode through process innovation. Compared with the existing technology, the electrode thickness is increased by 5 times, and 80% of the current collector support is abandoned. See US 61 / 736,798. Tesla's dry electrode technology evenly mixes the active material, conductive agent and binder, and then directly extrude the electrode membrane through high temperature and high pressure, and then composites it with the current collector. 24M's preparation of thick electrodes in the form of current collector + active material membrane will greatly deteriorate the electronic and ion conductivity of the electrode. The polarization impedance of the battery made with thick electrodes will be very large, and it cannot be charged and discharged at normal current density. Although the dry electrode technology eliminates the slurry process and avoids solvent consumption, it still consumes a lot of electricity in the high temperature and high pressure of the membrane extrusion molding process, and die-cutting and stripping are required for the final molding of the electrode. Both 24M's thick electrode technology and Tesla's dry electrode technology use the traditional pole piece structure. A large amount of copper and aluminum foil substrate will be used in the pole piece manufacturing process, which cannot effectively reduce weight and control material costs. Summary of the invention
[0005] The object of the present invention is to provide a pole piece and a preparation method thereof which are simple to manufacture, have reduced production costs and high production efficiency.
[0006] A first aspect of the present invention provides a method for preparing a pole piece, comprising the following steps:
[0007] (1) dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture;
[0008] (2) adding a solvent or no solvent to the solid substance mixture and stirring to obtain a viscous material;
[0009] (3) stamping the viscous material and the sheet-shaped metal electrode tab to obtain a wet electrode sheet;
[0010] (4) drying the solvent in the wet electrode to obtain a dry electrode;
[0011] (5) Pressing the dry electrode sheet to a thickness of 0.05-5 mm to obtain the electrode sheet; or
[0012] (1') dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture;
[0013] (2') heating the solid material mixture to soften the binder to obtain a softened material;
[0014] (3') stamping the softened material and the sheet-shaped metal tab to obtain a pre-pressed pole piece;
[0015] (4') Pressing the pre-pressed pole piece to a thickness of 0.05-5 mm to obtain the pole piece.
[0016] In one or more embodiments, the binder is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0017] In one or more embodiments, the solvent is N-methylpyrrolidone or water.
[0018] In one or more embodiments, the active material powder is lithium iron phosphate or graphite.
[0019] In one or more embodiments, the conductive agent is conductive carbon black.
[0020] In one or more embodiments, the metal wire is an aluminum wire or a copper wire.
[0021] In one or more embodiments, the length of the metal wire is 0.5-4 cm, such as 1-3 cm.
[0022] In one or more embodiments, the mass fraction of the metal wire in the solid matter mixture is 3%-15%.
[0023] In one or more embodiments, in step (1), in the solid material mixture, the mass fractions of the active material powder, the binder and the conductive agent are 80%-95%, 0.5%-5% and 0.5%-5%, respectively.
[0024] In one or more embodiments, in step (1), lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire are mixed into a solid material mixture, in which the mass fractions of lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire are 89%-93%, 1%-3%, 1%-3% and 3%-9%, respectively.
[0025] In one or more embodiments, in step (1), graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are mixed into a solid material mixture, in which the mass fractions of graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are 82%-90%, 0.5%-2%, 0.5%-2%, 0.5%-2% and 5%-15%, respectively.
[0026] In one or more embodiments, in step (2), when a solvent is added to the solid material mixture, the mass fraction of the solvent is >0% and ≤15%, based on the total mass of the viscous material.
[0027] In one or more embodiments, step (3) comprises: laying two or more layers of the viscous material in a mold, placing a sheet metal tab between two adjacent layers of the viscous material, and ensuring that the thickness of the two adjacent layers of the viscous material is the same.
[0028] Another aspect of the present invention provides a pole piece prepared using the method described in any embodiment of the present invention.
[0029] In one or more embodiments, the pole piece has a compacted density of 1-3 g / cc.
[0030] Another aspect of the present invention provides an electrochemical device, wherein the electrochemical device comprises the electrode piece described in any embodiment of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the process for preparing a viscous material in some embodiments of the present invention, wherein ① is a metal wire; ② is an active material powder; ③ is a binder; ④ is a conductive agent; ⑤ is a solvent; and ⑥ is a viscous material.
[0032] Figure 2 It is a schematic diagram of the electrode pressing and forming in some embodiments of the present invention, wherein ⑥ is a viscous material; ⑦ is a electrode. DETAILED DESCRIPTION
[0033] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a preferred technical solution.
[0034] The present invention provides a method for preparing an electrode, comprising the following steps:
[0035] (1) dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture;
[0036] (2) adding a solvent or no solvent to the solid substance mixture and stirring to obtain a viscous material;
[0037] (3) stamping the viscous material and the sheet-shaped metal tab to obtain a wet electrode;
[0038] (4) drying the solvent in the wet electrode to obtain a dry electrode;
[0039] (5) Press the dry electrode to a thickness of 0.05-5 mm to obtain the electrode.
[0040] The binder may be selected from one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR). In some embodiments, the binder is polyvinylidene fluoride. In some embodiments, the binder is carboxymethyl cellulose and styrene butadiene rubber. The solvent may be N-methyl pyrrolidone (NMP) or water. The active material powder may be lithium iron phosphate or graphite. The solvent and the binder may be selected according to the properties of the active material powder. In some embodiments, the active material powder is lithium iron phosphate; the solvent is NMP; the binder is polyvinylidene fluoride. In some embodiments, the active material powder is graphite; the solvent is water; the binder is carboxymethyl cellulose and styrene butadiene rubber. The conductive agent may be conductive carbon black (SP).
[0041] The metal of the metal wire is a metal with certain strength and electrical conductivity. Preferably, the metal wire is an aluminum wire or a copper wire. The length of the metal wire can be 0.5-4cm, for example 0.7-3.3cm, 1-3cm, 1.5-2.5cm. The metal wire can include a variety of metal wires of different lengths. In a preferred embodiment, the metal wire includes a metal wire with a length of 0.7-1.3cm, a metal wire with a length of 1.7-2.3cm, and a metal wire with a length of 2.7-3.3cm. In a preferred embodiment, in the metal wire, the mass ratio of the metal wire with a length of 0.7-1.3cm, the metal wire with a length of 1.7-2.3cm, and the metal wire with a length of 2.7-3.3cm is (2.5-3.5): (0.5-1.5): (0.5-1.5). In some embodiments, the length of all metal wires is 1.7-2.3cm.
[0042] The present invention eliminates the traditional current collector (such as copper and aluminum foil) used for pole piece support and current conduction, and directly adds metal wire (such as copper wire or aluminum wire) to the active material powder, binder and conductive agent for mixing, and then makes a viscous material. The pole piece prepared using this viscous material, because it is rich in metal wires inside, is similar to a reinforced concrete structure, and can play a good role in supporting and fixing the powder, thereby achieving self-support of the pole piece. The pole piece using this structure can greatly reduce the use of metal (such as copper and aluminum). It is estimated that the mass fraction of copper metal in the negative electrode can be reduced to less than 10%, and the mass fraction of aluminum metal in the positive electrode can be reduced to less than 5%.
[0043] In step (1), in the solid material mixture, the mass fraction of the metal wire can be 3%-15%, such as 5%-12%, 8%-10%, 6%-11% or 7%-9%. The mass fraction of the active material powder can be 80%-95%, such as 82%-92%, 85%-88%. The mass fraction of the binder can be 0.5%-5%, such as 1%-4% or 2%-3%. The mass fraction of the conductive agent can be 0.5%-5%, such as 1%-4% or 2%-3%. In some embodiments, in step (1), the active material powder is lithium iron phosphate, the binder is PVDF, the conductive agent is SP, and the metal wire is aluminum wire. In the solid material mixture, the mass fractions of lithium iron phosphate, PVDF, SP and aluminum wire are 89%-93%, 1%-3%, 1%-3% and 3%-9% respectively. Preferably, in the solid material mixture, the mass fractions of lithium iron phosphate, PVDF, SP and aluminum wire are 90%-92%, 1.5%-2.5%, 1.5%-2.5% and 4%-7%, respectively. The mass fraction of aluminum wire is preferably 2%-6%. In some embodiments, the active material powder is graphite, the binder is CMC and SBR, the conductive agent is SP, and the metal wire is copper wire. In the solid material mixture, the mass fractions of graphite, CMC, SP, SBR and copper wire are 82%-90%, 0.5%-2%, 0.5%-2%, 0.5%-2% and 5%-15%, respectively. Preferably, the mass fractions of graphite, CMC, SP, SBR and copper wire are 85%-88%, 1%-1.5%, 1%-1.5%, 1%-1.5% and 5%-15%, respectively. The mass fraction of copper wire is preferably 6%-13%.
[0044] In step (2), a solvent may or may not be added to the solid material mixture. When no solvent is added, the solid material mixture is mixed into a viscous material by a binder. When a solvent is added, the mass fraction of the solvent is greater than 0% and less than or equal to 15%, based on the total mass of the viscous material. Preferably, the mass fraction of the solvent in the viscous material is 0.1%-15%, for example, 0.5%, 2%, 5%, 8%, 10%, 12%. Different from traditional slurry mixing, the present invention proposes a new mixing method: first, the solid materials are dry mixed, and then no solvent or a small amount of solvent is added to the mixed solid material mixture, and it is mixed into a viscous material in a manner similar to kneading dough to obtain an ultra-high solid content viscous material. The ultra-high solid content viscous material obtained is used to prepare electrodes, which can greatly reduce the use of solvents.
[0045] In step (3), two or more layers of viscous material can be laid flat in the mold, for example, three, four, five, six or more layers of viscous material can be laid flat. A sheet metal pole ear is placed between two adjacent layers of viscous material. The material of the metal pole ear can be copper, aluminum or nickel. The thickness of the two adjacent layers of viscous material should be the same. The number of layers and thickness of the viscous material can be determined according to the thickness of the ultra-thick pole piece to be prepared. In some embodiments, if a pole piece with a thickness of 1.5 mm is to be prepared, the total thickness of each layer of the viscous material should be ≥1.6 mm. In some embodiments, if a pole piece with a thickness of 0.75 mm is to be prepared, the total thickness of each layer of the viscous material should be ≥0.8 mm.
[0046] In some embodiments, the present invention provides a method for preparing an electrode, comprising the following steps:
[0047] (1') dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture;
[0048] (2') heating the solid material mixture to soften the binder to obtain a softened material;
[0049] (3') stamping the softened material and the sheet-shaped metal tab to obtain a pre-pressed pole piece;
[0050] (4') Pressing the pre-pressed pole piece to a thickness of 0.05-5 mm to obtain the pole piece.
[0051] The definitions of active material powder, binder, conductive agent, tab and metal wire are as described in any embodiment herein.
[0052] In step (2'), the heating temperature may be 100-500° C., for example, 150° C., 200° C., 250° C., 300° C., 350° C., 400° C., 450° C., 500° C. The heating temperature may be selected according to the softening temperature of the selected binder.
[0053] In step (3'), two or more layers of softened material can be laid flat in the mold, for example, three, four, five, six or more layers of softened material. A sheet metal ear is placed between two adjacent layers of softened material. The thickness of the two adjacent layers of softened material should be the same. The number of layers and thickness of the softened material can be determined according to the thickness of the ultra-thick pole piece to be prepared. In some embodiments, if a pole piece with a thickness of 1.5 mm is to be prepared, the total thickness of each layer of the softened material should be ≥1.6 mm. In some embodiments, if a pole piece with a thickness of 0.75 mm is to be prepared, the total thickness of each layer of the softened material should be ≥0.8 mm.
[0054] The ultra-high solid content viscous material and / or softened material proposed in the present invention can realize one-step stamping of the pole piece. At the same time, the viscous material can greatly reduce energy consumption and shorten time during the drying process due to less solvent.
[0055] The present invention also provides a pole piece prepared by the method of the present invention. The thickness of the pole piece is between 0.05-5 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm. The compacted density of the pole piece of the present invention is 1-3 g / cc, for example, 1.5 g / cc, 2 g / cc, 2.5 g / cc. The pole piece prepared by the method of the present invention can be applied to lithium ion batteries, sodium ion batteries and other electrochemical devices requiring electrode structures.
[0056] Advantages of the present invention include:
[0057] (1) The method of the present invention greatly reduces the production process and directly realizes the electrode production by homogenization and one-step stamping, which greatly reduces the electrode production process and improves production efficiency.
[0058] (2) The method of the present invention uses ultra-high solid content slurry, which reduces the amount of solvent used, and can even eliminate the use of solvent, thereby reducing solvent costs. At the same time, it is easy to dry and reduces energy consumption.
[0059] (3) The method of the present invention eliminates the thin film current collector in the traditional electrode, and directly adds metal wire (such as copper wire or aluminum wire) to the slurry for mixing to achieve self-support and current collection of the electrode, which can significantly reduce the amount of metal (such as copper or aluminum) used in the electrode, save materials, and reduce costs.
[0060] (4) In the method of the present invention, the one-dimensional structural characteristics of the metal wire (such as copper wire or aluminum wire) avoid the barrier effect of the thin film current collector in the traditional electrode on the electrolyte infiltration and transmission, shortening the electrolyte infiltration time and the transmission path of the electrolyte replenishment during the cycle.
[0061] (5) The method of the present invention can realize the manufacture of ultra-thick electrodes with a thickness ranging from 50 to 5000 μm.
[0062] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by weight.
[0063] In the present invention, the method for measuring compacted density is as follows:
[0064] Compacted density = (pole piece weight - substrate weight) / (sampling area*(pole piece thickness - substrate thickness)).
[0065] In the present invention, metal wire is used to replace the current collector in the traditional process. When testing the compaction density of the electrode obtained in Examples 1-3 of the present invention, the substrate weight is the total weight of the metal wire used in preparing the electrode, the substrate thickness = metal wire volume / sampling area, and the metal wire volume = total metal wire weight / metal density.
[0066] Example 1: Preparation of lithium iron phosphate electrode
[0067] Lithium iron phosphate, PVDF, SP and aluminum wire are dry-mixed in a mass ratio of 91.5:1.9:1.6:5, wherein the aluminum wire is composed of three lengths of 1 cm, 2 cm and 3 cm in a mass ratio of 3:1:1.
[0068] After the solid material is evenly mixed, NMP is added as a solvent, wherein the mass ratio of the solvent to the solid material is 1:9. After the solvent is added, kneading and stirring are performed until it becomes viscous, and the dry powder in the solid-liquid mixture is all wetted. At this time, it can be determined that the solid-liquid mixture is evenly mixed, and a viscous material is obtained.
[0069] Spread the mixed viscous material flat in the mold, place the sheet metal Al pole ear on the flat viscous material, and then spread a layer of slurry to ensure that the thickness of the upper and lower layers of slurry are consistent. The thickness of each layer of slurry is at least 0.8mm. Finally, stamp it into shape to obtain a wet pole piece.
[0070] After stamping, the solvent in the wet electrode is dried to obtain a dry electrode, and finally the dry electrode is placed in a mold and pressed to a thickness of 1.5 mm.
[0071] The compacted density of the pole piece of Example 1 was measured to be 2.5 g / cc.
[0072] Example 2: Preparation of graphite pole piece
[0073] Graphite, CMC, SP, SBR and copper wire were dry-mixed in a mass ratio of 86:1.35:1.35:1.3:10, wherein the copper wire consisted of three lengths of 1 cm, 2 cm and 3 cm in a mass ratio of 3:1:1.
[0074] After the solid substances are mixed evenly, distilled water is added as a solvent, wherein the mass ratio of the solvent to the solid substances is 1:9. After the solvent is added, kneading and stirring are performed until the mixture becomes viscous, and the dry powder in the solid-liquid mixture is all wetted. At this time, it can be determined that the solid-liquid mixture is evenly mixed, and a viscous material is obtained.
[0075] Spread the mixed viscous material flat in the mold, place the sheet metal Cu pole ear on the flat viscous material, and then spread a layer of slurry to ensure that the thickness of the upper and lower layers of slurry are consistent. The thickness of the two layers of slurry is at least 0.4mm. Finally, stamp and form to obtain the wet pole piece.
[0076] After stamping, the solvent in the wet electrode is dried to obtain a dry electrode. Finally, the dry electrode is placed in a mold and pressed to a thickness of 0.75 mm.
[0077] The compacted density of the pole piece of Example 2 was measured to be 1.5 g / cc.
[0078] Example 3: Preparation of lithium iron phosphate pole piece
[0079] The pole piece of Example 3 was prepared according to the method of Example 1. The only difference between Example 3 and Example 1 is that all the aluminum wires used were 2 cm in length.
[0080] The thickness of the pole piece prepared in Example 3 is 1.5 mm, and the compaction density of the pole piece is measured to be 2.5 g / cc.
[0081] Comparative Example 1: Preparation of lithium iron phosphate pole piece
[0082] Lithium iron phosphate, PVDF, SP and NMP were mixed in a mass ratio of 57.9:1.2:0.9:40 to prepare a slurry.
[0083] The mixed slurry is coated on both sides of the aluminum foil, and an empty foil area without coating is reserved on the aluminum foil. The thickness of the slurry coated on both sides of the aluminum foil is consistent, and 0.18 mm of slurry is coated on both sides to obtain a wet electrode, in which the mass of the aluminum foil accounts for 10% of the total mass of lithium iron phosphate, PVDF, SP and aluminum foil.
[0084] The solvent in the wet electrode is dried to obtain a dry electrode, and finally the electrode is pressed to 0.22 mm by a roller pressing device, which is the maximum thickness that can be achieved by traditional processes.
[0085] The compaction density of the pole piece of Comparative Example 1 was measured to be 2.5 g / cc.
[0086] Comparative Example 2: Preparation of graphite pole piece
[0087] Graphite, CMC, SP, SBR and water were mixed in a mass ratio of 47.85:0.5:0.75:0.9:50.
[0088] The mixed slurry is coated on both sides of the aluminum foil, and an empty foil area without coating is reserved on the aluminum foil. The thickness of the slurry coated on both sides of the aluminum foil is consistent, and 0.12mm of slurry is coated on both sides to obtain a wet electrode, in which the mass of the aluminum foil accounts for 10% of the total mass of graphite, CMC, SP, SBR and aluminum foil.
[0089] The solvent in the wet electrode is dried to obtain a dry electrode, and finally the electrode is pressed to 0.18 mm by a roller pressing device, which is the maximum thickness that can be achieved by traditional processes.
[0090] The compaction density of the electrode sheet of Comparative Example 2 was measured to be 1.5 g / cc.
Claims
1. A method for preparing a pole piece, characterized in that: The following steps are involved: (1) dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture; (2) adding a solvent to the solid substance mixture and stirring to obtain a viscous material; (3) stamping the viscous material and the sheet-shaped metal electrode tab to obtain a wet electrode; (4) drying the solvent in the wet electrode to obtain a dry electrode; (5) Pressing the dry electrode sheet to a thickness of 0.05-5 mm to obtain the electrode sheet; or (1') dry-mixing active material powder, a binder, a conductive agent and metal wire to obtain a solid material mixture; (2') heating the solid material mixture to soften the binder to obtain a softened material; (3') stamping the softened material and the sheet-shaped metal tab to obtain a pre-pressed pole piece; (4') Pressing the pre-pressed pole piece to a thickness of 0.05-5 mm to obtain the pole piece; Wherein, the metal wire is an aluminum wire or a copper wire, and the length of the metal wire is 0.5-4 cm.
2. The preparation method according to claim 1, characterized in that The method has one or more of the following features: The binder is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose and styrene-butadiene rubber; The solvent is N-methylpyrrolidone or water; The active material powder is lithium iron phosphate or graphite; The conductive agent is conductive carbon black.
3. The preparation method according to claim 1, characterized in that: In the solid matter mixture, the mass fraction of the metal wire is 3%-15%.
4. The preparation method according to claim 1, characterized in that In step (1), in the solid material mixture, the mass fractions of the active material powder, the binder and the conductive agent are 80%-95%, 0.5%-5% and 0.5%-5% respectively.
5. The preparation method according to claim 1, characterized in that: In step (1), lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire are mixed into a solid material mixture, wherein the mass fractions of lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire in the solid material mixture are 89%-93%, 1%-3%, 1%-3% and 3%-9% respectively; or In step (1), graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are mixed into a solid material mixture, in which the mass fractions of graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are 82%-90%, 0.5%-2%, 0.5%-2%, 0.5%-2% and 5%-15%, respectively.
6. The preparation method according to claim 1, characterized in that: In step (2), when a solvent is added to the solid material mixture, the mass fraction of the solvent is greater than 0% and less than or equal to 15%, based on the total mass of the viscous material.
7. The preparation method according to claim 1, characterized in that: Step (3) comprises: laying two or more layers of the viscous material in a mold, placing a sheet metal tab between two adjacent layers of the viscous material, and ensuring that the thickness of the two adjacent layers of the viscous material is the same.
8. A pole piece prepared using the method according to any one of claims 1 to 7.
9. The pole piece according to claim 8, characterized in that: The compacted density of the pole piece is 1-3 g / cc.
10. An electrochemical device, characterized in that: The electrochemical device comprises the electrode piece according to claim 9.
Citation Information
Patent Citations
Electrochemical slurry compositions having high rate capability
US61736798P0
Self-supporting conductive wire electrode, preparation method thereof and lithium air battery
CN109921038A
Flexible battery and preparation method and application thereof
CN112531176A